Foundations for Fitness: A Multi-Cohort Pediatric Weight Management Intervention - Morrison, Kyle M.; Smith, Steven (International Journal of Child Health and Nutrition, 2021)
This study examined the benefits of a 10-week childhood obesity intervention program on various measures of health. The program involved parents and children who met once weekly for two hours. Each session of the intervention program consisted of a structured dynamic warm-up an aerobic exercise component in a game play setting and a motor-skill specific instruction period. Subjects were recruited from pediatrician recommendation and a total of 99 subjects (n=48 boys, n=51 girls) completed both pretest and posttest intervention measures. The mean age was 9.86 (SD=0.02 years). Each of the following were assessed on pediatric assessment prior to and following the intervention program: height, weight, body mass index (BMI), waist circumference, resting heart rate, resting blood pressure, habitual physical activity, percent body fat, and quality of life. Assessment of the participant’s cardiovascular fitness and the state of home environment in regards to nutrition and physical activity were completed as part of the first and tenth (final) intervention program sessions. Results indicated that the changes observed that were statistically significant included the categories of systolic blood pressure, height, weight, quality of life, habitual physical activity, FNPA score, and PACER scores. Improvements in outcomes measured were modest but this result was expected due to the short intervention program of only ten-weeks duration. Recommendations include increasing the length of the intervention and conducting follow-up assessment to determine long-term impact.